Recent Advancements and Challenges in Medical Laser Applications: From Diagnosis to Treatment - Hussein, Ahmed Faris Hamoud; Hassan, Abdul-Muhaimin Ahmed; Eisaa, Nawras Ismail Majeed; Abood, Batool Ali Tarish (American Journal of Botany and Bioengineering, 2025)
Laser technology has undergone remarkable advancements, revolutionizing various sectors of medicine, including diagnostics, surgery, and therapy. Despite widespread application, challenges persist in fully optimizing laser-tissue interaction, improving safety, and expanding cost-effective access to laser-based treatments. This article provides a comprehensive review of medical laser applications, covering historical development, types of medical lasers, and modern innovations such as fiber lasers, diode lasers, and laser-based imaging techniques. The analysis reveals that lasers have significantly improved the precision, minimally invasive nature, and therapeutic effectiveness of procedures, especially in dermatology, oncology, ophthalmology, and surgery. However, findings also highlight challenges related to regulatory barriers, training requirements, and equitable access. The study concludes that interdisciplinary collaboration, technological innovation, and adherence to safety protocols are essential for maximizing the potential of medical lasers in enhancing patient care.